Inflation Expectations and Firm Decisions: New Causal Evidence. Issue 1 (16th September 2019) - Coibion, Olivier; Gorodnichenko, Yuriy; Ropele, Tiziano
Abstract: We use a unique design feature of a survey of Italian firms to study the causal effect of inflation expectations on firms' economic decisions. In the survey, a randomly chosen subset of firms is repeatedly treated with information about recent inflation whereas other firms are not. This information treatment generates exogenous variation in inflation expectations. We find that higher inflation expectations on the part of firms leads them to raise their prices, increase demand for credit, and reduce their employment and capital. However, when policy rates are constrained by the effective lower bound, demand effects are stronger, leading firms to raise their prices more and no longer reduce their employment.